On contact conformal curvature tensor in LP-Sasakian manifolds - Shah, Riddhi Jung (BIBECHANA, 2017)
The purpose of the present paper is to study the contact conformal curvature tensor in LP-Sasakian manifolds. Some properties of contact conformally flat, ξ -contact conformally flat and contact conformally semi-symmetric LP-Sasakian manifolds are obtained.BIBECHANA 15 (2018) 24-29